The effects of TeaCrine® and caffeine on endurance and cognitive performance during a simulated match in high-level soccer players - Bello, M. L.; Walker, A. J.; McFadden, B. A.; Sanders, D. J.; Arent, S. M. (Journal of the International Society of Sports Nutrition, 2019)
Background: Theacrine (1,3,7,9-tetramethyluric-acid) is a pure alkaloid with a similar structure to caffeine and acts comparably as an adenosine receptor antagonist. Early studies have shown non-habituating effects, including increases in energy and focus in response to Teacrine®, the compound containing pure theacrine. The purpose of this study was to determine and compare the effects of Teacrine® and caffeine on cognitive performance and time-to-exhaustion during a simulated soccer game in high-level male and female athletes. Methods: Male and female soccer players (N = 24; MAge = 20.96 ± 2.05y, MMaleVO2max = 55.31 ± 3.39 mL/O2/kg, MFemaleVO2max = 50.97 ± 3.90 mL/O2/kg) completed a 90-min simulated treadmill soccer match over four randomized sessions (TeaCrine®, caffeine, TeaCrine® + caffeine, placebo). Cognitive testing at halftime and end-of-game including simple reaction time (SRT), choice RT (CRT), and cognitive-load RT with distraction questions (COGRT/COGRTWrong) was performed, with a run time-to-exhaustion (TTE) at 85% VO2max following end-of-game cognitive testing. Session times and pre-exercise nutrition were controlled. RM-MANOVAs with univariate follow-ups were conducted and significance was set at P < 0.05. Results: TTE trended towards significance in TeaCrine® and TeaCrine® + caffeine conditions compared to placebo (P < 0.052). A condition main effect (P < 0.05) occurred with faster CRT in caffeine and TeaCrine® + caffeine compared to placebo. COGRTWrong showed a significant time main effect, with better accuracy at end-of-game compared to halftime (P < 0.05). A time x condition interaction in SRT (P < 0.05) showed placebo improved from halftime to end-of-game. Conclusions: The 27-38% improvements in TTE reflect increased performance capacity that may have important implications for overtime scenarios. These findings suggest TeaCrine® favorably impacts endurance and the combination with caffeine provides greater benefits on cognitive function than either supplement independently